Effect of salinity on survival, feed intake and growth of Clarias batrachus (Linn.) fingerlings - Sahoo, S K; Giri, S S; Maharathi, C; Sahu, A K (Indian Journal of Fisheries, 2011)
Effects of different levels of salinity (2, 4, 6, 8 and 10 ppt) on survival, feed intake and growth of freshwater clariid, Clarias batrachus were studied in a thirty days laboratory experiment. Although the fingerlings tolerated the salt level in water between 0 and 4 ppt, severe mortality was observed beyond 6 ppt after 7-23 days of rearing. No significant (P<0.05) differences with regard to feed intake and body weight gain were observed when reared in 0 and 2 ppt salinity. However, feed intake and specific growth rate were decreased with the increase of salinity. Salinity level above 4 ppt was found to be detrimental to fish and in turn they lost their body weight. However, it is inferred that Clarias batrachus fingerlings can be reared in 2 ppt saline water without any adverse effect on growth, survivability and biomass production